Assessment of the miscanthus gasification in a semi-industrial gasifier using a CFD model. (August 2017) - Monteiro, Eliseu; Ismail, Tamer M.; Ramos, Ana; Abd El-Salam, M.; Brito, P.S.D.; Rouboa, Abel
Highlights: Numerical model used in the gasification of agro-industrial waste in Portugal. Portuguese miscanthus was studied by using a semi-industrial gasification plant. The effect of ER, temperature and steam-to-biomass ratio were assessed. Numerical and experimental results are in good agreement. Abstract: In this work, a comprehensive two-dimensional computational fluid dynamics model was used in order to assess the potential of syngas produced from gasification of Portuguese miscanthus by using a semi-industrial gasification plant. An Eulerian-Eulerian approach is used in the fluent environment to describe the transport of mass exchange, momentum and energy for both solid and gas phases. The results were obtained after comparing both the numerical model and the experimental data for validation. The simulated syngas composition was found to be in good agreement with the experiment. The effect of equivalent ratio (ER), temperature and steam-to-biomass ratio (SBR) on products of gasification and their concentrations were assessed. The ER has some negative effects on syngas quality (decrease of fuel gases and lower heating value (LHV)) and some positive effect on the carbon conversion efficiency (CCE) and on the reduction of tar content. The reactor temperature has a positive effect on syngas quality (increase of fuel gases, lower heating value and decrease of tars). High temperatures also favor the gasification efficiency. The SBR has some positive effects on syngas quality (increase of H2 content and reduction of tars) and some negative effect on syngas LHV and there are some particular SBR that maximizes the CCE and CGE.